Internalization of Moral Values in the Frame of International School - Partono - -; Wifda Untsa Nailufaz; Uswatun - Khasanah; Nur Anisa Amala Widyastuti; Sinta Ulliyana Hidayatika (STAI Hubbulwathan Duri, 2021)
This study aims to see how the process of internalizing moral values in Indonesian Foreign Schools, in this case, the Dutch Indonesian School in The Hague (SIDH). The research method used is descriptive qualitative with data collecting techniques such as interviews and documentation. The results showed that the moral values facilitated by SIDH include social values (which are reflected in honesty, responsibility, cooperation, tolerance, and peace, among others), religious values (which are reflected in obedience to worship and how to get along with the opposite sex by the teachings Islam). The value of nationalism (reflected in students while maintaining and introducing Indonesian culture in the Netherlands). Being present and developing in the Land of Windmills is not a barrier to continuing education by adhering to national values. Education does not deprive students of the roots of tradition or national moral values wherever education is located.